Cloud computing review: Features and issues - Al-Ahmad, Ahmad Salah; Kahtan, Hasan (IEEE, 2018)
Cloud computing is an on-demand network selfservice, dynamic power and virtual resources. It provide elasticity, restrictions and interactivity which introduces many new features and issues. This paper will review cloud computing common features and issues mainly in term of security. Security has been selected to be the focus of this paper due to high interest in security form both academics and inducts. This paper has categorized cloud computing feature into three categories i.e. technology, economy, and on-Technology. On the other hand this paper has categorized the cloud computing security issues into five categories i.e. infrastructure, data, access, compliance, and provider. This paper provides researchers and industry an insight about the cloud features and issues that may help them in directing their research and mplementation of technologies and provide categorization for cloud computing features and issues, which can be expanded while the cloud computing technology advances